Churchill's Ministry of Ungentlemanly Warfare the mavericks who plotted Hitler's defeat - Milton, Giles (New York Picador, 2014)
In the spring of 1939, a top-secret organization was founded in London: its purpose was to plot the destruction of Hitler?s war machine, through spectacular acts of sabotage.
Includes bibliographical references (pages 335-339) and index.
Keywords: Gubbins, Colin, Sir, 1896-1976.